Project Monitoring and Evaluation in the Sustainability of Donor-Funded Potato Projects in Kabale District, Uganda - Turyasingura, John Bosco; Moses, Agaba; Meza, Orach; Zombeire, Regis; Kyabarongo, Benon (American Journal of Humanities and Social Sciences Research (AJHSSR), 2022)
High Points  The study is about the effect of potato project design and implementation in the sustainability of donor funded potato projects in Kabale District and there is minimal participation of potato farmers in project monitoring and evaluation in the sustainability of donor-funded potato projects in Kabale District.  The essence of potato project monitoring and evaluation in the sustainability of donor-funded potato projects in Kabale District is to increase knowledge and improve the livelihoods of potato farmers without wasting donors’ resources after donor exit.  It was found out that, there is the participation of potato project farmers in monitoring and evaluation with vital for the sustainability of donor-funded potato projects in Kabale District Background: This study was set to determine the effect of project monitoring and evaluation on the implementation of funded potato projects in the Kabale District. Monitoring and evaluating a strategic role of communities that equips potato project beneficiaries to feel that they have a stake in the project. However, monitoring and evaluation activities by the communities have not been entirely accepted by donors. Objective: This study was set to determine the effect of project monitoring and evaluation on the implementation of funded potato projects in the Kabale District. Methods: This study adopted a descriptive survey design, and it used potato farmers as the unit of analysis. Data was collected in the means of administering a questionnaire survey from a sample of 196 potato farmers. Structural equation modeling was used to test hypotheses. Results: Findings revealed that project monitoring and evaluation have significant positive relationship sustainability of funded potato projects Conclusion and Recommendations: The study concludes that; Project monitoring and evaluation should be participatory. Therefore, the study recommends that project beneficiaries should share information concerning their project, collect data together and learn lessons from the project report and disseminate data for purposes of understanding very well the project